Atypical features of benign rolandic epilepsy in Chinese children: Retrospective study. Issue 7 (July 2017) - Zhao, Xiuhe; Wang, Aiqin; Wang, Shengjun; Zhang, Tongxia; Chi, Zhaofu; Liu, Yiming
Abstract: Background: Benign rolandic epilepsy (BRE) is one of the most common focal epilepsies in childhood, but less typical clinical presentations may lead to misdiagnosis and incorrect treatment. The focus of this study was therefore to retrospectively investigate the less typical features of BRE in Chinese children. Methods: Data on 316 Chinese children with BRE were collected and analyzed. Results: A total of 7.3% of children complained of tension, fear and terror at the onset of a seizure, and 5.4% had been misdiagnosed with mesial temporal lobe epilepsy. Approximately 12.3% had post‐ictal Todd's paresis, with 6.6% having been misdiagnosed and given incorrect treatment. Nineteen children (6%) had neuroradiologic abnormalities, which could lead to a diagnosis of symptomatic epilepsy. Twenty‐five patients (8.0%) had cognitive deficits. Conclusions: Greater recognition of, and further investigation into, the spectrum of BRE are needed.